Transfer of electrocoagulation technology knowledge for the treatment of petroleum based industrial wastewater - Faten Ahada, Mohd Azli; Abdul Aziz, Mohd Azoddein; Mazrul Nizam, Abu Seman; Agus Sahar, Abdul Hamid; Tahfiz, Tajuddin; Said, N. (2017)
This programme is aimed to transfer the knowledge and technology of electrocoagulation to treat industrial wastewater. Every kind of industry will release wastewater either in small or large amount depending on size of industry. Concentration of organic and inorganic contaminants is commonly high in industrial wastewater and various type of treatment is being used based on the concentration and types of contaminants. The focus of this knowledge transfer programme is to treat petroleum based industry wastewater using electrocoagulation. Petroleum based industry is chosen because this industry is one of important industry in Malaysia especially in East Coast region. For this programme, electrocoagulation reactor system will be enhanced in order to transfer the technology to MY Synergy Factors (M) Sdn. Bhd. Then, knowledge transfer training will be organized for the industry personnel to introduce them appropriate optimum operating parameters and Standard Operating Procedure (SOP) in handling the new electrocoagulation reactor for wastewater treatment. This knowledge transfer program will bring benefit in term of economic gain to the industry. Other than that, the collaboration between industry and university will become closer.